The new encyclopedia británica in 30 volumes, macropedia VOL. 9 / William Benton - Benton, William (1977)
Humidity indices, relation between temperature and humidity, humidity and climate, humidity and human affairs, the logic of laughter, laughter and emotion, situational humour, styles and techniques in humour, relations to art and science, the humanization of humour, form the outbreak of war to the peace of bretigny, from the peace of bretigny to the accession of henry v, from the accession of henry v to the siege of Orleans.